IDENTIFIKASI GYMNOSPERMAE DI GUNUNG SARI, KECAMATAN SALAM, KABUPATEN MAGELANG SEBAGAI BUKU REFERENSI - Puspitasari, Vani; Permadani, Karunia Galih; Kusumaningrum, Serafica Btari Christiyani (FKIP Universitas Tanjungpura, 2025)
This study aims to evaluate the feasibility of a biology reference book designed to identify Gymnospermae species at Gunung Sari. The research employed a mixed‐methods approach comprising two phases. The first phase was a descriptive exploratory study to identify the Gymnospermae species present. The second phase involved development research using the 4 D model by Thiagarajan, limited to three stages, Define, Design, and Develop. The results revealed nine species of Gymnospermae at Gunung Sari. In the feasibility tests, the content and media experts rated the reference book at 85 % and 88 %, respectively, both falling into the “very feasible” category. The readability test conducted among students and the general public yielded scores of 87.6 % and 89.3 %, also categorized as “very feasible.” Furthermore, the overall expert evaluation by plant biosystematics lecturers achieved a score of 83.5 %, likewise rated “very feasible.” It is concluded that the reference book is highly suitable to serve as an informational resource about Gymnospermae for the general public